PENERJEMAHAN BROSUR WISATA MONUMEN SIMPANG LIMA GUMUL DALAM BAHASA JEPANG SEBAGAI MEDIA PROMOSI DI WORKSHOP TRAINING CENTER - Aziz, Moh. Faizal Fuad; Chomsiyah, Irawati (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2023)
Tourism potential in Kediri is a monument of Simpang Lima Gumul (SLG), which is famous for its shape that resembles the Arc de Triomphe in Paris. This monument is an icon from Kediri city that needs to be developed with promotional efforts for Japanese tourists. Moreover, there are quite frequent visits by native Japanese to the institution of the Japanese Language Course (WTC) in Kediri's Kampung Inggris. This study aimed to describe the creation of SLG monument brochures in Japanese. The methods of the study used included problem analysis, data collection, and media design. The result of this study was a tourist brochure of the SLG monument in Japanese as a promotional medium for WTC. Through this promotion, it is hoped that Japanese tourists' visits to SLG will increase. This brochure can be given to native Japanese speakers who visit the English Village Course Institute, namely the Workshop Training Center. Practically this brochure will be useful as a guide sheet that will make it easier for Japanese tourists travelling to Simpang Lima Gumul.Keywords: Brochure; Simpang Lima Gumul; Japanese.